The effects of emotion and COVID-19 context priming on the size and color of drawings: based on human figure drawings and tree drawings - Cao, Huijing; Zhang, Xiaohan; Zhang, Xinlei; Yan, Wenhua (Frontiers in Psychology, 2023)
Introduction This study aimed to investigate the effects of emotional themes and the COVID-19 pandemic context priming on the size and color of drawings. Methods A 3 (emotion: peacefulness, gratitude, loneliness) × 2 (context: pandemic, regular) mixed design was used and 113 university students in Shanghai were recruited to draw human figures and trees using 10 marker colors. Results The size of the drawings depicting loneliness was smaller than that of the those depicting peacefulness and gratitude. Drawings depicting loneliness used more cool and non-preferred colors; drawings depicting gratitude used more warm and preferred colors. Drawings in the pandemic context were larger, which may reflect the more significant threat perceived by individuals. Drawings in the pandemic context used more red colors, showing symbolic meanings such as danger. Discussion The drawing size and drawing color are influenced by emotional themes and the pandemic context priming.